Production of HPP natural hydrogels from conventional and non-conventional starch sources - Katerina Koshenaj; Giovanna Ferrari; Giovanna Ferrari (Frontiers in Food Science and Technology, 2025)
Starches from conventional sources such as cereal crops, pulses, and tubers have been widely utilized to produce starch-based hydrogels, which are complex networks able to absorb and retain substantial amounts of water. However, in recent years due to the increasing interest to produce these biomaterials, also starches derived from non-conventional sources have gained attention. In this study, conventional and non-conventional starches isolated from pea flour, lentil flour, unripe apples, and banana peels were used to produce starch-based hydrogels by high-pressure processing (HPP). The starch powders were isolated through traditional methods and showed high starch content (76.91%–86.56%) and minimal starch damage. According to their amylose content, ranging from 18.74% to 22.42%, these starches were classified as normal starches. Starch suspensions (25% w/w in distilled water) were treated at 600 MPa for 15 min at room temperature to enable starch gelatinization. Gel formation was assessed by analysing the gelatinization extent, structuring level, and swelling power of the samples. Furthermore, the physical appearance and flow profile of the obtained structures were evaluated. The results indicated that the starch-based hydrogels produced under these processing conditions exhibited different gel formation levels, physical appearance, and flow behaviour. These differences were attributed to the distinct properties of the recovered starches. More work is needed to assess the mechanical properties and physical stability of these structured materials during shelf life.